Effects of Cichorium Intybus Linn on Blood Glucose, Lipid Constituents and Selected Oxidative Stress Parameters in Streptozotocin-Induced Diabetic Rats - Samarghandian, Saeed; Borji, Abasalt; Hidar Tabasi, Seyed (Cardiovascular & Haematological Disorders - Drug Targets, 2013)
The efficacy of herbal medicine has been confirmed in treatment of diabetes mellitus (DM) by amelioration of oxidative stress. The present study was designed to investigate protective effects of Cichorium intybus extract (CIE) against oxidative damage in diabetic rats. In this study, the rats were divided into the control (C), diabetic (D), D + CIE– treated (125 mg/kg/day) groups. Male Sprague–Dawley rats aged 9 weeks (160 ± 15 g) were administered with streptozotocin (STZ, 60 mg/kg) intraperitoneally (ip) to induce experimental diabetes. From 3 days after STZ administration to the end of the study (4 weeks) the ethanolic extract of CIE was administered (i.p) to diabetic rats. Body weight and blood glucose were measured weekly. At the end of the 4-week period, blood was drawn for biochemical assay, in order to determine the changes of cellular antioxidant defense system, serum oxidative damage and serum lipid were measured profile. CIE injection to diabetic rats resulted in significant reduction in blood glucose, triglyceride (TG), total cholesterol (TC), low density lipoprotein cholesterol (LDL-C) levels and significant elevation high density lipoprotein cholesterol (HDL-C) level as well as increase in the body weight as compared with the rats treated with STZ alone. In the treated diabetic group, we also observed the significant increase in reduced glutathione (GSH), superoxide dismutase (SOD), glutathione-S-transferase (GST) and catalase (CAT) with decline in malondialdehyde (MDA) level compared with the non-treated diabetic group. These results suggest that the Cichorium intybus extract has antioxidant properties and prevents diabetes complications by modulation of oxidative stress system.
Keywords: oxidative stress